Multisite Scenarios of Black Carbon and Biomass Burning Aerosol Characteristics in India - Vivek Kumar; Panuganti C. S. Devara; Vijay K. Soni (Aerosol and Air Quality Research)
Abstract Black Carbon (BC) aerosols are not only substantial climate-forcing drivers but also impact human health. The spatial distribution of BC aerosols depends on the combination of anthropogenic activities and meteorological conditions. In this study, we used the India Meteorological Department (IMD) Black Carbon Observational Network datasets to assess the diurnal, seasonal, and long-term BC trends for the period, 2016–2021. The majority of the IMD’s BC monitoring stations show an overall declining trend in the BC mass concentration during the study period in India. Maximum BC concentrations are observed in the post-monsoon and winter seasons due to the stubble-burning activity and lower values of Atmospheric Boundary Layer Height (ABLH). Minimum concentrations are observed at all stations in the monsoon season due to the wet scavenging of aerosols by rain. There is a clear decrease in the BC mass concentration from winter to monsoon months and an increase in the post-monsoon months. Regional emissions from crop residue burning in the post-harvesting seasons are the main contributing factor for extremely high levels of BC mass concentration. Low wind speed and shallow mixed layer were found to be the main reasons for high levels of aerosol concentration during the winter season. There is an increasing trend in Biomass Burning (BB) at most of the stations except for Thiruvananthapuram, where a prominent decreasing trend in BC concentration is also noticed. In the present study, the impact of local meteorological parameters such as wind, temperature, rainfall and Atmospheric Boundary Layer Height on BC mass concentration is investigated. The results show a negative correlation with rainfall, relative humidity, wind speed, temperature and ABL height. Both local activity and long-range transport at each study site are also found to be responsible for the significant changes in BC mass concentration.